Rancang Bangun Pembelajaran Jaringan Server dengan Sistem Server Cloud Virtual (Hypervisor) - Putra, Toni Wijanarko Adi (Jurusan Teknologi Informasi Universitas Semarang, 2019)
Computers now have very high capabilities so they can be used virtualization. With computer capabilities that are high enough computer lab practicum and server administration can already be done on a pc or laptop that has virtualization applications installed. Network practicum and server administration that previously could only be done in the classroom, so with this technology it is expected that it can be practiced on a PC or personal laptop for each student, so that students are able to continue the practical scenario that has been given. Virtualization will use Hyper-V that already exists in Windows 7, Windows 8 and Windows 10. In the Hyper-V application 4 Windows servers will be installed, all of which will be installed and connected via Active Directory. All windows servers will be accessed using a computer and physical network through the Remote Desktop Connection application. So it is expected that with this study student will be able to practice outside the campus lab environment.